Penggunaan ChatGPT dalam Pengerjaan Tugas Kuliah Mahasiswa Program Studi Komunikasi Digital dan Media - Nabil Aqil Fakhrisya Ramadhan; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology encourages the use of Artificial Intelligence (AI), such as ChatGPT, in students' academic activities, especially for searching for references, generating ideas, summarizing materials, and assisting in the preparation of assignments. This study aims to describe the use of ChatGPT in completing assignments for students of the Digital Communication and Media Study Program and to determine students' assessment of the benefits of its use. This study uses a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to 39 students of the Digital Communication and Media Study Program who had used ChatGPT in completing academic assignments. Data analysis was carried out using descriptive statistics with a Likert scale and calculation of average scores. The results showed that the use of ChatGPT in completing assignments was in the high category with an overall average score of 4.21. Most respondents gave a positive assessment of the use of ChatGPT, as indicated by the percentage of respondents who agreed and strongly agreed on each indicator, which was between 79.5% and 92.3%. ChatGPT was considered to help students in generating ideas, understanding and summarizing materials, composing academic writing, increasing the efficiency of assignment work, saving time, and simplifying the assignment preparation process. The majority of students continue to check and edit the results provided by ChatGPT as a form of academic responsibility. Based on the research findings, it can be concluded that ChatGPT is utilized as an aid in completing academic assignments and makes a positive contribution to the student learning process. Its use can improve time efficiency, simplify assignment preparation, and support understanding of the material without replacing students' role in critical thinking and maintaining academic integrity.